Challenges and Opportunities of Teaching in Multilingual and Multicultural Education Contexts in Namibia (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
This study investigated the challenges and benefits of teaching in Namibia’s multilingual and multicultural educational contexts. A sample of 30 teachers was purposefully selected for the current study. The data were collected through focus group discussions and a self-administered questionnaire and analysed using a thematic data analysis method. The findings show that teachers have difficulties in serving learners from various cultures and languages, which creates challenges to inclusive learning settings. Although the teachers (participants) experienced difficulty in assessing learners’ oral tasks, it emerged that their cultural awareness and language proficiency increased. The study emphasises the significance of a comprehensive training plan in multicultural learning programmes for developing cultural competency and preparing teachers for multilingual and multicultural settings.
Keywords: Distance learning; Diverse Cultures; Inclusive Education; Kunene Region; Learning environment; Multicultural language; Multilingual